Bankruptcy : the case for relief in an economy of debt / Joseph Spooner. - Spooner, Joseph Tobias, 1985- (International corporate law and financial market regulation., 2019)
A decade after the Global Financial Crisis and Great Recession, developed economies continue to struggle under excessive household debt. While exacerbating inequality and political unrest, this debt - when combined with wage stagnation and a shrinking welfare state - has played a key role in maintaining economic growth and allowing households faced with rising costs of living to make ends meet. In Bankruptcy: The Case for Relief in an Economy of Debt, Joseph Spooner examines this economic model and finds it increasingly unsustainable. In a call to action to reduce debt burden, he turns to bankruptcy law, which is uniquely situated as a mechanism of social insurance against the risks of a debt-dependent economy. This book should be read by anyone interested in understanding the problem of consumer debt and how best to address it.